De- Westernizing Media Theory to Make Room for African Experience - Nyamnjoh, Francis B. (Popular Media, Democracy and Development in Africa, 2010)
How should one think about popular media in the African context? Should we attempt to understand and analyse the increasing proliferation of tabloids, reality television shows, pop music, websites and mobile communications through the analytical frameworks constructed by scholars in the Global North, or does Africa pose unique research questions? Is there a danger of either essentializing Africa by treating her as ‘different’, or by ignoring her specificity by approaching her media via Western theoretical constructs? The scholar wishing to understand the interface between popular media, development and democracy in contemporary African societies is faced with a complex double bind. Elsewhere (Nyamnjoh 2005: 2-3) I have argued that African worldviews and cultural values are doubly excluded from global media discourses, first by the ideology of hierarchies and boundedness of cultures, and second by cultural industries more interested in profits than the promotion of creative diversity and cultural plurality. Little attention is accorded to how Africans negotiate and navigate the various identity margins and cultural influences in their lives, in ways that are not easily reducible to simple options or straightforward choices. The consequence of rigid dichotomies or stubborn prescriptiveness based on externally induced expectations of social transformation is an idea of democracy hardly informed by popular articulations of personhood and agency in Africa, and media whose professional values and content are not in tune with the expectations of those they purport to serve. The predicament of media practitioners in such a situation, as well as those wishing to understand African media practice through media theory, is obvious: to be of real service to liberal democracy and its expectations of modernity, they must ignore alternative ideas of personhood and agency in the cultural communities within which such practices take place and of which such practitioners and, often, scholars form part. Attending to the interests of particular cultural groups as strategically essential entities risks contradicting the principles of liberal democracy and its emphasis on civic citizenship and the autonomous individual, which media practitioners in African societies are being held accountable to.
Num Pages: 13
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

ALT 36: Queer Theory in Film and Fiction: African Literature Today - Emenyonu, Ernest N.; Hawley, John C. (Boydell & Brewer, 2018)
"Debates on the future of the African continent and the role of gender identities in these visions are increasingly present in literary criticism forums as African writers become bolder in exploring the challenges they face and celebrating gender diversity in the writing of short stories, novels, poetry, plays and films. Controversies over the rights of Lesbian, Gay, Bisexual, Trans, Intersex, Queer (LGBTIQ) communities in Africa, as elsewhere, continue in the context of criminalization and/or intimidation of these groups. Residual colonial moralizing and contemporary western identity norms and politics vie with longstanding polyvalent indigenous sexual expression. In addition to traditional media, the new social media have gained importance, both as sources of information exchange and as sites of virtual construction of gender identities. As with many such contentious issues, the variety of responses to the "state of the question" is strikingly visible across the continent. In this issue of ALT, guest editor John Hawley has sampled the ongoing conversations, in both African writing and in the analysis of contemporary African cinema, to show how queer studies can break with old concepts and theories and point the way to new gender perspectives on literary and cinematic output. This volume also includes a non-themed section of Featured Articles and a Literary Supplement."–Publisher's description
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice LGBTQ+; 5-Identités diasporiques; _Nettoyé

Documentary Practice and Transnational Feminist Theory - White, Patricia (A Companion to Contemporary Documentary Film, 2015)
This paper looks at five documentaries on activism around ending the practice of female genital cutting (FGC) in Africa. All were made by or in partnership with UK and US producers and are distributed by the New York-based non-profit media arts organization Women Make Movies. By tracing changing political and representational strategies in feminist documentaries on the issue and the varying terms on which the films engage their subjects and address their viewers, the chapter aims to put the specificity of independent documentary formats, practices, and institutions in dialogue with feminist theoretical critiques of the wider discourse on women's human rights. The chapter looks at Kaplan and Grewal's critique of the neo-colonialism of Alice Walker and Pratibha Parmar's Warrior Marks, the observational strategies of Kim Longinotto's The Day I Will Never Forget, the diasporic dimensions of Mrs. Goundo's Daughter and Sarabah, and the visual rhetoric of human rights models in Equality Now's Africa Rising. The cultural field of documentary constitutes a public sphere in which activist and theoretical debate, contested reception, and continually renewed cultural production articulate the productively shifting terms of transnational feminism.
Section: 10 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781118884584.ch10
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé